Biological features of Spodoptera litura fed on three vegetable host plants under controlled laboratory conditions - MELANIE MELANIE; WAWAN HERMAWAN; HIKMAT KASMARA; FIRTRIA YUNITASARI; CAMELLIA PANATARANI; I MADE JONI (Smujo International, 2024)
Abstract. Melanie M, Hermawan W, Kasmara H, Yunitasari F, Panatarani C, Joni IM. 2024. Biological features of Spodoptera litura fed on three vegetable host plants under controlled laboratory conditions. Nusantara Bioscience 16: 297-303. Mass-rearing insects is necessary for biological control research, supporting the insect populations for effective in-vitro bioassay evaluations. The success of mass culture depends on the quality of insect feeding and environmental conditions. Spodoptera litura (Fabricius, 1775) larvae are notorious as major pests in horticultural crops. This study investigates the feeding preferences and developmental outcomes of S. litura larvae when fed on 3 different host plants (water spinach, spinach, and cabbage) with distinct nutritional compositions. The larvae were reared in a controlled insect-rearing cabinet, with parameters observed host-plant nutrition, total consumption, larval weight gain, and developmental duration from larvae to imago. The experimental design employed a completely randomized design with 3 host plants and 9 replications, analyzed with ANOVA and Duncan's multiple-range test. Results indicate that 4th-5th instar larvae showed highly consumed water spinach leaves compared to early larvae, which significantly preferred cabbage leaves. Larvae fed on water spinach leaves achieved the highest average weights for larvae, pupae, and imago, along with accelerated developmental times. However, no significant differences were observed in weight gain or developmental duration to imago among all feeding treatments. In conclusion, water spinach is an appropriate host plant for the controlled mass rearing of S. litura.